Pengaruh komponen kurikulum ilmu siasah syar'iyyah dalam kursus teras universiti - Azizi Umar,; Noor Hisham Md Nawi, (Universiti Kebangsaan Malaysia, 2012)

(untitled)
This article aims to discuss the extent to which the formation of siasah syar'iyyah curriculum components in the core courses of universities such as Citizenship or Malaysian Studies, the Islamic civilization through TITAS courses, courses in Islamic Studies and Ethnics Relations. The purpose of teaching political science have almost similar to the siasah syar'iyyah these courses. The study also wish knew integration and severability of terms in the curriculum in public and private universities. Study of document analysis and experience of the writer as teaching shows that the courses are taught separately and seem to have nothing to do with the concept of political integration of knowledge in siasah syar'iyyah course epistemologhy while still discuss matters related to the concept and political thought. Taught political science while also being in a state separated from the original source of the continuity of siasah syar'iyyah. Knowledge integration relationship is also quiet loose with the continuity of the history of Islam in Malaysia. The study also found that the discipline of knowledge gaps, whereas the history of Islam also is the power of authority granted to the State besides being the official religion of the Federation of the Constitution. The author proposes a new course called 'Ketatanegaraan Islam" was introduced at the College and the University of Islam as a new discipline for the initial step.